2010
DOI: 10.1002/yea.1821
|View full text |Cite
|
Sign up to set email alerts
|

A new yeast genetic resource for analysis and breeding

Abstract: We made a library of Saccharomyces cerevisiae F 1 hybrids from all possible crosses of 16 wild-type strains, including two common laboratory strains and two commercial winemaking varieties. Fourteen of the starting strains have been sequenced. Thus, the sequences of both genomes are known in 182 novel hybrids, and the sequence of one genome is known in 56. All tested strains sporulated. Fertilities were in the range 0-100%. Hybrids showed no more variation than parental strains for ethanol production, ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…Previous studies involving yeast hybrids have observed heterosis (Timberlake et al, 2011;Zorgo et al, 2012), but not to the extent reported here. The presence of a single loss-of-function mutation per hybrid is consistent with finding many partially and fully dominant hybrids, as suggested by Zorgo et al (2012), but not with the amount of overdominant hybrids found here.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies involving yeast hybrids have observed heterosis (Timberlake et al, 2011;Zorgo et al, 2012), but not to the extent reported here. The presence of a single loss-of-function mutation per hybrid is consistent with finding many partially and fully dominant hybrids, as suggested by Zorgo et al (2012), but not with the amount of overdominant hybrids found here.…”
Section: Discussioncontrasting
confidence: 87%
“…On the other hand, when Y397 segregants were crossed with Y141 or Y354 segregants, several hybrids showing a significant best-parent heterosis effect for IA production were identified (e.g., H44 showed a 45% increase of IA). Such best-parent heterosis has already been observed for other phenotypes in S. cerevisiae hybridization experiments (26,27), but it does not seem to occur for all traits (28). However, it was recently shown that best-parent heterosis occurs relatively frequently when genetically distant domesticated strains are crossed, while the incidence is lower in wild strains (29).…”
Section: Discussionmentioning
confidence: 81%
“…The four F 1 hybrids were constructed between a homozygous ura-derivative of M2 and homozygous lys-derivatives of BC187, L-1528, S288c and Y55. Hybridisation was performed in this laboratory by Timberlake et al (2010).…”
Section: Methodsmentioning
confidence: 99%